A Study of Importance for Analyzing and Understanding the Firm's External Environment in Delhi: Analyzing the Impact of External Environment and Firm Capabilities on Performance: A Study on Large Scale Manufacturing Firms in Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper will be conceptualizing relationship between external environment, firm capabilities, strategic responses and performance in Delhi. External environment will be argued that it positively influences performance. Other perspectives have posited that firm capabilities moderate the choice of strategic choice. However, some empirical studies have contradicted these influences hence the need for more research on the effect of firm capabilities on the external environment in Delhi. These variables were contextualized in large scale manufacturing firms in Delhi. The broad objective of the study will be to determine the influence of firm capabilities and strategic responses on the external environment and performance of large scale firms in Delhi. The specific external environment on performance, determine the influence of external environment on strategic responses, determine the influence of strategic responses on performance, determine the effect of strategic responses on the external environment establish the effect of firm capabilities external environment and lastly, establish the joint effect of external environment, firm capabilities performance of large scale manufacturing firms in Delhi.